2014
DOI: 10.1152/ajpendo.00257.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute lipid overload on skeletal muscle insulin resistance, metabolic flexibility, and mitochondrial performance

Abstract: Dubé JJ, Coen PM, DiStefano G, Chacon AC, Helbling NL, Desimone ME, Stafanovic-Racic M, Hames KC, Despines AA, Toledo FG, Goodpaster BH. Effects of acute lipid overload on skeletal muscle insulin resistance, metabolic flexibility, and mitochondrial performance. Am J Physiol Endocrinol Metab 307: E1117-E1124, 2014. First published October 28, 2014; doi:10.1152/ajpendo.00257.2014.-We hypothesized that acute lipid-induced insulin resistance would be attenuated in highoxidative muscle of lean trained (LT) enduranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 52 publications
3
70
2
Order By: Relevance
“…Similarly, lipid overload, often used as a model for insulin resistance (Brehm et al, 2006; Itani, 2002; Yu, 2002), may represent a model of metabolic flexibility rather than revealing a pathological mechanism of insulin resistance. In support of this, Phelix et al and Dube et al demonstrated in independent studies (Dube et al, 2014; Phielix et al, 2012) that endurance-trained athletes who have a high oxidative capacity in muscle can increase fatty acid oxidation in response to lipid overload, but they preserve glycogen storage within muscle at the expense of decreasing glucose oxidation (Figure 1, data obtained from ( Dube et al, 2014)). This enhanced metabolic flexibility was associated with a higher mitochondrial capacity in exercise-trained muscle (Dube et al, 2014; Phielix et al, 2012).…”
Section: Skeletal Muscle Insulin Resistance and Fatty Acid Metabolismmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, lipid overload, often used as a model for insulin resistance (Brehm et al, 2006; Itani, 2002; Yu, 2002), may represent a model of metabolic flexibility rather than revealing a pathological mechanism of insulin resistance. In support of this, Phelix et al and Dube et al demonstrated in independent studies (Dube et al, 2014; Phielix et al, 2012) that endurance-trained athletes who have a high oxidative capacity in muscle can increase fatty acid oxidation in response to lipid overload, but they preserve glycogen storage within muscle at the expense of decreasing glucose oxidation (Figure 1, data obtained from ( Dube et al, 2014)). This enhanced metabolic flexibility was associated with a higher mitochondrial capacity in exercise-trained muscle (Dube et al, 2014; Phielix et al, 2012).…”
Section: Skeletal Muscle Insulin Resistance and Fatty Acid Metabolismmentioning
confidence: 74%
“…In support of this, Phelix et al and Dube et al demonstrated in independent studies (Dube et al, 2014; Phielix et al, 2012) that endurance-trained athletes who have a high oxidative capacity in muscle can increase fatty acid oxidation in response to lipid overload, but they preserve glycogen storage within muscle at the expense of decreasing glucose oxidation (Figure 1, data obtained from ( Dube et al, 2014)). This enhanced metabolic flexibility was associated with a higher mitochondrial capacity in exercise-trained muscle (Dube et al, 2014; Phielix et al, 2012). Recent evidence also suggests that circadian variation in the molecular metabolic machinery can influence metabolic flexibility (Bass and Lazar, 2016).…”
Section: Skeletal Muscle Insulin Resistance and Fatty Acid Metabolismmentioning
confidence: 74%
“…With respect to mitochondria, it has been reported that mitochondrial respiration (21), mitochondrial biogenesis (32), and perhaps oxidative capacity and energy production decline with aging. However, it's generally accepted that aerobic exercise training, in both older (9) and younger (11) previously sedentary subjects, results in enhanced mitochondrial oxidative capacity. In agreement with data from Proctor et al (39), we did not observe any differences in mitochondrial capacity between the cohorts in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, skeletal muscle mitochondria play a specific role in exercise capacity 2 , aging 3 , degenerative disease 4 and Type II diabetes 5 . As an aging society, and Type II Diabetes being the 7 th leading cause of death in the United States 6 , the need for methods that assess mitochondrial function has become increasingly more prevalent in biomedical research 7,8 .…”
Section: Introductionmentioning
confidence: 99%